1992
DOI: 10.1021/np50082a003
|View full text |Cite
|
Sign up to set email alerts
|

Directed Biosynthesis of Unnatural Ergot Peptide Alkaloids

Abstract: Three unnatural lysergic derivatives belonging to the class of ergopeptines have been obtained by feeding L-norvaline to a strain of Claviceps purpurea. Ergorine {!] corresponds to an analogue of ergovaline, and ergonorine {2} is an analogue of ergocornine; both have at C-5' an ß-propyl substituent instead of an isopropyl group. Ergonomorine [3] has the npropyl group at C-2' and C-5' as well. This alkaloid represents the first example of an ergopeptine having an unnatural amino acid in the first position of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The known "ergot alkaloids" produced by Clauiceps spp. may be divided into five major classes: the clavine, lysergic acid, simple lysergic acid amides, ergopeptine, and ergopeptam alkaloids (Berde and Schild, 1978;Perellino et al, 1992Perellino et al, , 1993. The ergopeptines, simple lysergic acid amides, and clavines (Figures 1, 5, and 6 ) have been isolated from A. coenophialum-infected tall fescue (Yates et al, 1985;Lyons et al, 1986;Petroski and Powell, 1991).…”
Section: A Coenophialum-infected Fescuementioning
confidence: 99%
“…The known "ergot alkaloids" produced by Clauiceps spp. may be divided into five major classes: the clavine, lysergic acid, simple lysergic acid amides, ergopeptine, and ergopeptam alkaloids (Berde and Schild, 1978;Perellino et al, 1992Perellino et al, , 1993. The ergopeptines, simple lysergic acid amides, and clavines (Figures 1, 5, and 6 ) have been isolated from A. coenophialum-infected tall fescue (Yates et al, 1985;Lyons et al, 1986;Petroski and Powell, 1991).…”
Section: A Coenophialum-infected Fescuementioning
confidence: 99%
“…2). Since the alkaloid production depends primarily on the relative concentration of free amino acids in cells (Beacco et al, 1978;Bianchi et al, 1982;Crespi-Perellino et al, 1992;Cvak et al, 1996;Flieger et al, 1984;Keller et al, 1980), the comparison of the homo-Ile/Leu ratio in the amino acid pool, Table 3, with that in the corresponding alkaloids, i.e. Ergot alkaloids are synthetized by a multienzyme system extraribosomally (Maier et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…:34 It was found that lochnericine (36) and lochnerinine (37) were metabolites, which were presumably sequentially formed. Metabolism of ajmaline (38) by cell cultures of R. serpentina has been found to yield raumacline (39) and its derivatives ( 40) and (41), which are new alkaloids. 35 Illustration is hereby provided of the ability of cell cultures to make new compounds which may be of biological interest and application.…”
Section: Terpenoid Indole Alkaloidsmentioning
confidence: 99%